If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6 = 7(x + -1) Reorder the terms: 6 + 7x = 7(x + -1) Reorder the terms: 6 + 7x = 7(-1 + x) 6 + 7x = (-1 * 7 + x * 7) 6 + 7x = (-7 + 7x) Add '-7x' to each side of the equation. 6 + 7x + -7x = -7 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + 0 = -7 + 7x + -7x 6 = -7 + 7x + -7x Combine like terms: 7x + -7x = 0 6 = -7 + 0 6 = -7 Solving 6 = -7 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x-1/2=5/4 | | -x+2=29 | | 12/10n=7/6 | | 14=6+z(-2) | | 2v-10=2 | | 0.08x-0.28=-4.8+1.2x-3.2x | | (5x+3)(2x-4)= | | -3/4b=2 | | 2a+2ab= | | 3p+8=1 | | x/6-4=-6 | | -5/6+g=17/3 | | (x+3)+1/2x=20 | | 5(x+4)/3=2x-2 | | 3.1x=22.94 | | -11/12w=-1 | | y^123=x+2 | | 7x-3x=14 | | 0.80x+0.10(140)=0.40(49) | | 36x^3y+33x^2y+6xy=0 | | X+2=2(4-x) | | x+13-2x=0 | | -16t^2+48t+864=t | | x+3+x=20 | | 4/9+y=4 | | 60-6x=8x-18 | | 3/4x+5/4=-7/4 | | 42+(-51)= | | 8h-19=69 | | x^14=y^152+362 | | 60x-6=8x-18 | | 118-3x=15x+16 |